2019
DOI: 10.1021/acs.macromol.9b00251
|View full text |Cite
|
Sign up to set email alerts
|

Constraint Release Mechanisms for H-Polymers Moving in Linear Matrices of Varying Molar Masses

Abstract: We investigate the influence of the environment on the relaxation dynamics of well-defined Hpolymers diluted in a matrix of linear chains. The molar mass of the linear chain matrix is systematically varied and the relaxation dynamics of the H-polymer is probed by means of linear viscoelastic measurements, with the aim to understand its altered motion in the different blends, compared to its pure melt state. Our results indicate that short unentangled linear chains accelerate the relaxation of both the branches… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
39
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(44 citation statements)
references
References 77 publications
5
39
0
Order By: Relevance
“…Most of these models predict chain relaxation in the so-called terminal regime of the viscoelastic behavior, where, e.g., within a DTD mechanism, the tube would reach its final dilated value. Accordingly, the experimental studies are usually based on macroscopic rheological or dielectric techniques (see, e.g., [9][10][11][12][13]). A direct experimental microscopic observation of the time dependence of the CR or DTD mechanisms remains elusive [14,15].…”
mentioning
confidence: 99%
“…Most of these models predict chain relaxation in the so-called terminal regime of the viscoelastic behavior, where, e.g., within a DTD mechanism, the tube would reach its final dilated value. Accordingly, the experimental studies are usually based on macroscopic rheological or dielectric techniques (see, e.g., [9][10][11][12][13]). A direct experimental microscopic observation of the time dependence of the CR or DTD mechanisms remains elusive [14,15].…”
mentioning
confidence: 99%
“…for the case of star polymers diluted in a linear matrix. While eqs and yield very similar results if the linear matrix is not too entangled ( Z linear < 10), they largely differ if longer matrices are used . However, these equations were not tested in this regime, which is difficult to reach experimentally.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, we investigated the viscoelastic properties of a H-polymer diluted in linear matrices of different molar masses and concentration . When diluted in an oligomeric matrix at concentration low enough to avoid self-entanglements, it was found that the terminal relaxation of the H backbone was well described by a Rouse process, but with a delay θ H due to the extra friction coming from the branches attached to the backbone.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…An active area of research for polymer solutions and melts containing both branched and linear polymers is to understand how the presence of a linear chain matrix influences the relaxation of branched chains. In the linear viscoelastic regime, significant progress has been made and different theoretical models describe accurately the effects of adding branched polymers into a linear matrix [7][8][9][10]. Actually, a recent study by R. Hall et al has shown that when the linear polymer has a relaxation time longer than the star component, the terminal relaxation time dependence has non-monotonic dependence on the blend composition, and this result is obtained both theoretically and experimentally [11].…”
Section: Introduction and Theoretical Backgroundmentioning
confidence: 99%